IMPLEMENTASI METODE VIKOR DALAM PEMILIHAN KEPALA SEKOLAH BERPRESTASI PADA DINAS PENDIDIKAN SUMATERA UTARA - Wulan, Sri; Nadeak, Berto; Hondro, Rivalri Kristianto; Waruwu, Fince Tinus (STMIK Budi Darma, 2018)
North Sumatra Office of education through the Directorate General of Teachers conducting the election of the head of the school is doing, with these activities the North sumatra Office of education hope school principals have success in education, so demanding to renew the social and professional attitude in managing education led. The election of the head of school is done to be able to improve quality and manage in school education so that it could be improved, so that it is able to answer the challenges of the global era-based excellence. The selection process should be free from the interests of religion, tribe or region. So that the final results of the election, do not cause harm to either party. But in pelaksanaanya there are some parties who feel aggrieved because of the lack of transparency of the assessment process and clear terms for the election of the head of school achievers. Resolve the problem then need to built a decision support system (SPK) which is able to provide the ability to solve problems with the condition of semi structured and unstructured. Use the perangkingan method, it is expected that it may facilitate in providing the principal election decision accomplished using VIKOR. The results obtained in this study is an alternative that has been dirangkingkan. Based on the results of the rank of produced output that is the names of the principal performer.Keywords: Head Of School Achievers, Decision Support System, VIKOR Method